An aurivillius oxide based cathode with excellent CO2 tolerance for intermediate-temperature solid oxide fuel cells - Zhu, Y.; Zhou, W.; Chen, Y.; Shao, Zongping (Wiley-VCH Verlag, 2016)
The Aurivillius oxide Bi2Sr2Nb2MnO12-d (BSNM) was used as a cobalt-free cathode for intermediate-temperature solid oxide fuel cells (IT-SOFCs). To the best of our knowledge, the BSNM oxide is the only alkaline-earth-containing cathode material with complete CO2 tolerance that has been reported thus far. BSNM not only shows favorable activity in the oxygen reduction reaction (ORR) at intermediate temperatures but also exhibits a low thermal expansion coefficient, excellent structural stability, and good chemical compatibility with the electrolyte. These features highlight the potential of the new BSNM material as a highly promising cathode material for IT-SOFCs.